FACTORS TO CONSIDER IN PROMOTING HIGH ADOPTION OF CLIMATE CHANGE ADAPTATION STRATEGIES: EVIDENCE FROM NORTHERN GHANA - Akudugu, M. A.; Al-hassan, S.; Adam, H. (UDS International Journal of Development, 2019)
This paper identified and examined the factors that climate change policy makers and implementers need to consider in their attempts to promote high adoption of climate change adaptation strategies in Ghana, with specific focus on northern Ghana where endemic poverty is exacerbated by the adverse effects of climate change. Based on multiple stage sampling the paper considered 300 farm households from 17 farming communities for the analyses. The study employed a binary model (Probit) to identify the determinants of high adoption of climate change adaptation strategies among farmers in northern Ghana. Gender of household head, household head education level, household size, participation in climate change trainings, perception of yield increases, geographic location, access to credit and membership to farmer-based organisations were the factors considered in the Probit model. The result revealed that many farmers are high adopters of climate change adaptation strategies (CCASs) and this is good news for policy makers and implementers. Gender of household head, awareness or access to information on climate change, yield increases and membership to farmer-based organisations are the critical factors that significantly influence the decisions of farmers to adopt high levels of climate change adaptation strategies. Farmer-based organisations should be used as springboards and/or platforms for the promotion of adoption of climate change adaptation strategies among farmers. Interventions to promote and sustain high adoption of CCASs must take into consideration the heterogeneity and geographical locations of beneficiary farmers and communities. Keywords:Â Adaptation, Climate Change, Probit Model, Farm Households